PENGARUH PERMAINAN TEROWONGAN ANGKA TERHADAP KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI PAUD AS-SHIFA CITRA KECAMATAN TAMPAN KOTA PEKANBARU - Yunita Puspa Sari; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This study aims to determine the effect of Tunnel Game Figure To Counting Ability Of Child Aged 5-6 Years In Paud As-Shifa Citra Tampan Sub District Pekanbaru City. The population in this study that children B classes totaling 25 children and sample in this study amounted to 25 children. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. This type of instrument used in this study is to use the observation and documentation to take notes about events that occurred during the treatment given. Based on the results obtained by testing the hypothesis that there are significant Tunnel Game Figure To Counting Ability Of Child Aged 5-6 Years In Paud As-Shifa Citra Tampan Sub District Pekanbaru City. This known t count 11.431 or significance (0.000), because sig < 0.05, it can be concluded that there are differences in the ability to know counting ability on students significant before and after using Tunnel Game Figure in the learning. Hypothesis testing can be seen on t = 11.431 > table = 2,064. It has been suggested that there are significant differences in the results between the pretest and posttest. Tunnel Game Figure To Counting Ability Of Child Aged 5-6 Years In Paud As-Shifa Citra Tampan Sub District Pekanbaru City amounted to 60,4%.Keyword: Counting, Tunnel Game Figure2